Council of Europe Mission. Conflict Impact with Russia - Mecaj, Stela (European Scientific Journal, ESJ, 2022)
Over the years, international organizations have played critical roles in the interactions and relationships that develop within the international system between and among states. The Russian Federation joined the Council of Europe in 1996 to strengthen its democratic policies. The nature of Russia’s membership in the Council of Europe is somewhat paradoxical, given how far it strayed from the organization’s objectives and principles. This also includes the organization’s credibility and ability to promote democratic values throughout the Russian Federation by applying the European Convention on Human Rights. In light of the latest developments in the conflict with Russia, the issue of the protection of human rights and fundamental freedoms, on which the Council of Europe is mainly focused, seems to be a key point in the European debate and beyond. This paper summarized all points where the Council of Europe deviated from its principles and objectives. The Council of Europe, among others, has to strengthen its authority and become more resilient to afford future crises. The main question of this paper is directly related to the research strategy which is the first element. The general question of this paper is as follows: Can the mission and purpose of the Council of Europe be considered fulfilled in any case of the existence of this organization?